2016
DOI: 10.1002/hpm.2387
|View full text |Cite
|
Sign up to set email alerts
|

Growing concerns and controversies to Taiwan's National Health Insurance—what are the lessons from mainland China, South Korea and Singapore?

Abstract: It has been over 20 years since Taiwan's implementation of its National Health Insurance (NHI) program. Under this program, the health insurance coverage rate has reached approximately 99% of the population. Despite guaranteeing the residents of Taiwan equal access regardless of socioeconomic status and background, critical problems and controversies persist, and they continue to challenge the NHI. We analyze the primary issues facing the NHI program with emphasis on financial and consumer behavioral aspects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…The study on the effect of insurance usage have often been conducted. The results of the study showed a positive correlation (El-Sayed, Vail and Kruk, 2018;Johar et al, 2018;Lee et al, 2018). Note: (a) The reference category was "no utilization"; (b) Floating point overflow occurred while computing this statistic.…”
Section: Resultsmentioning
confidence: 82%
“…The study on the effect of insurance usage have often been conducted. The results of the study showed a positive correlation (El-Sayed, Vail and Kruk, 2018;Johar et al, 2018;Lee et al, 2018). Note: (a) The reference category was "no utilization"; (b) Floating point overflow occurred while computing this statistic.…”
Section: Resultsmentioning
confidence: 82%
“…For example, Taiwan's universal health‐care system has been highly regarded; however, because its health‐care system does not provide a robust gatekeeper system, people could consistently seek unnecessary health care when they are not seriously ill . Hence, more than 30 000 insured residents in Taiwan made over 100 health‐care services per year . As the Chinese health‐care system does not have an effective gatekeeper system, a condition similar to Taiwan's could occur in China because the results of this study indicated a positive association between preventive care utilization and outpatient treatment expenses.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, such behavior is evident in other Asian regions. For example, Taiwan's universal health‐care system has been highly regarded; however, because its health‐care system does not provide a robust gatekeeper system, people could consistently seek unnecessary health care when they are not seriously ill . Hence, more than 30 000 insured residents in Taiwan made over 100 health‐care services per year .…”
Section: Discussionmentioning
confidence: 84%
“…Various studies in several countries on the impact of ownership of health insurance have found findings that have increased the use of health services that is far better (Lee et al, 2018) (Tilahun et al, 2018) (Miraldo, Propper and Williams, 2018) (Müllerschön et al, 2019). The same conditions apply to Indonesia (Mubasyiroh, Nurhotimah and Laksono, 2016) (Laksono, Wulandari and Soedirham, 2019b).…”
Section: Discussionmentioning
confidence: 91%